Analysis of the Role of Student-Based Political Programmes in University-Based Radio Stations in Kenya (Global Journal of Human-Social Science, 2025)
University radio stations that air student-based political programmes act as an essential medium in students politics enhancing media and democracy in universities This paper examines the role of student-based political programmes in MMUST FM a university radio station The study is guided by the democratic participant media theory by McQuail 1987 which emphasizes access to localized media by local users The study utilized a cross-sectional mixed research design which enabled the survey to collect quantitative and qualitative data from a diverse group of individuals simultaneously The study aimed at a population of 10311 undergraduates from the main campus using a quantitative approach 31 student leaders and three political programme producers using a qualitative approach The study used systematic random stratified and purposive sampling to select respondents First quantitative data was collected via questionnaires and presented using tables and graphs In contrast qualitative data was collected through focus group discussions targeting 31 student leaders and three in-depth interviews targeting radio political content producers at the radio station Qualitative data is presented using narration and quotes Descriptive and inferential statistics were used to analyze quantitative data and qualitative data was analyzed thematically based on emerging themes informed by research objectives The study findings indicate that student-based political programmes have provided the student community with a robust political platform on campus However MMUST FM s news editorial policy must emphasize news stories affecting the student community The study recommends that MMUST FM review its editorial policy to cover political news affecting the student community
Keywords: political advertising; political dialogue; political opinion; political voice; student-based political programmes; university-based radio stations